2011
DOI: 10.1113/expphysiol.2011.058941
|View full text |Cite
|
Sign up to set email alerts
|

Slow wave propagation and plasticity of interstitial cells of Cajal in the small intestine of diabetic rats

Abstract: The number of myenteric interstitial cells of Cajal (ICC-MY), responsible for the generation and propagation of the slow wave in the small intestine, has been shown to decrease in diabetes, suggesting impairment of slow-wave (SW) propagation and related motility. To date, however, this expected decrease in SW propagation has neither been recorded nor analysed. Eleven rats were treated with streptozotocin and housed in pairs with 11 age-matched control animals. After 3 or 7 months, segments of duodenum, jejunum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…The purpose of that study was to correlate the expected decrease in slow wave propagation with the reported decrease in the census of ICC-MY in the small intestine (8,10,20,30). To our initial surprise, we did not measure a significant decrease in slow wave propagation although there was a reduction in the number of ICC-MY by ϳ50% (10).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The purpose of that study was to correlate the expected decrease in slow wave propagation with the reported decrease in the census of ICC-MY in the small intestine (8,10,20,30). To our initial surprise, we did not measure a significant decrease in slow wave propagation although there was a reduction in the number of ICC-MY by ϳ50% (10).…”
mentioning
confidence: 88%
“…Animal preparations, electrical recordings, and data analysis were presented previously in detail (10). In brief, 11 male young adult Wistar rats were treated with an intraperitoneal injection of STZ at 60 mg/kg and housed together with 11 age-matched control rats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful reexamination of observations shall provide the next steps for understanding pathophysiology. For example, there is loss of ICCs in diabetes mellitus, but after a period, these cells may grow back (22). Given the intrinsic ability of ICCs to respond to stem cell factor, multicellular apoptosis in the gut wall in diabetes (9,22), as well as regenerative responses (22), merits aggressive examination.…”
mentioning
confidence: 99%
“…For example, there is loss of ICCs in diabetes mellitus, but after a period, these cells may grow back (22). Given the intrinsic ability of ICCs to respond to stem cell factor, multicellular apoptosis in the gut wall in diabetes (9,22), as well as regenerative responses (22), merits aggressive examination. Arguments should rise above semantic reconciliation and be directed at dissecting pathophysiology of gastrointestinal motility disorders to expand the currently limited therapeutic options.…”
mentioning
confidence: 99%